Generación de versiones especializadas de la wikipedia - García Moreira, Mario (2009)
In this work, is presented an alternative to generate an specialized encyclopedia with topics previously defined based on Wikipedia, using Hadoop library and the Amazon Web Services for the distributed processing of the original encyclopedia, so the generated results could be saved in a portable device to be consulted in any computer without a connection to Internet